Effect of a magnetic field on the adsorptive removal of methylene blue onto wheat straw biochar. (April 2016) - Li, Guoting; Zhu, Weiyong; Zhang, Chunyu; Zhang, Shen; Liu, Lili; Zhu, Lingfeng; Zhao, Weigao
Highlights: Adsorption of MB by wheat straw biochar was enhanced by a magnetic field. The biochar pyrolyzed at 200 °C outperformed those pyrolyzed at higher temperatures. The surface acidic functional groups were sensitive to the external magnetic field. Kinetic study indicated a chemisorption process of adsorption. The q max value was enhanced by 34.1% under the external magnetic field. Abstract: Biochar pyrolyzed from wheat straw was innovatively used for the adsorptive removal of cationic dye methylene blue through exposure to a magnetic field. The adsorption capability of the biochar pyrolyzed at 200 °C exceeded that of samples pyrolyzed at higher temperatures. The surface acidic functional groups of wheat straw biochar were deduced to be more sensitive to the effects of the external magnetic field. The enhancement of the magnetic field achieved by increases in the initial dye concentration, and a decrease in the biochar dosage and solution pH, were more significant compared with those caused by other conditions. Kinetic experiments indicated that chemisorption occurred during adsorption. The q max values for dye adsorption without, and with, an external magnetic field were found to be 46.6 and 62.5 mg/g, respectively. These demonstrated that wheat straw biochar could be used for the efficient adsorption of pollutants when assisted by an external magnetic field.